Association between uric acid and non-alcoholic fatty liver disease in patients with hypertension - Yan Zhao; Zhenwei Wang; Yang Liu; Ting Yang; Zhuang Li; Ao Gao; Lei Cao; Chongyang Ma (PLoS ONE, 2026)
Serum uric acid (UA) is linked to non-alcoholic fatty liver disease (NAFLD), but its role in hypertensive populations remains unclear. This cross-sectional study investigated their association in 1,058 patients with hypertension. Multivariate logistic regression analysis confirmed that UA was independently correlated with NAFLD, whether as a continuous variable or a categorical variable. According to the fully adjusted model, the risk of NAFLD increased by 0.2%, 347.2% and 91.7% for each unit increase in UA, Log 10 UA and LnUA, respectively (P < 0.05). Multivariate stratified analysis revealed that UA increased the risk of NAFLD in specific subgroups, including males, individuals aged 70–79 years, non-smokers, those without diabetes, and obese individuals (P < 0.05). Receiver operating characteristic (ROC) analysis indicated that UA could not only predict the occurrence of NAFLD but also improve the predictive value of the baseline model for NAFLD (UA, AUC: 0.588; baseline model, AUC: 0.770; baseline model + UA, AUC: 0.772). In conclusion, UA is significantly associated with NAFLD in patients with hypertension and may serve as a predictive risk indicator.